Construction risk control technology of a large tunnel complex in urban area - Gao, Xinqiang; Kong, Chao; Wu, Daifeng; Lu, Feng; Liu, Maoyi; Wang, Haiyan; Ren, Songbo (Frontiers in Earth Science, 2022)
The stability of the surrounding rock analysis and evaluation during tunnel construction is the basis of tunnel construction risk control. In this paper, we focus on the stability of a large-scale transportation tunnel complex during its construction in a densely-populated urban area. The tunnel complex includes seven shallow-buried tunnels with large cross-sections. In order to gain insight into the excavation influence of the different tunnels, stability analyses were first carried out using FLAC3D numerical simulation. Results showed that the tunnels were subjected to heave and crown settlement induced by adjacent excavation. Also, stress concentrated in the rock blocks connecting different tunnels. Subsequently, a bench-scale model test was performed to understand the failure of the rock blocks and to examine the accuracy of the numerical simulation. The test results agreed well with the numerical simulation. Based on the numerical and test results, the mechanism of the rock blocks failure was explained and construction risk control technology to stabilize the rock blocks was proposed. The construction risk analyses revealed: 1) tunnels are subjected to significant heave due to the excavation of tunnels located above; 2) the stability of the rock blocks is the paramount determinant for stabilizing the whole tunnel complex; 3) ensuring rock blocks to be in a state of triaxial stress is conducive to its stability and hence the stability of multiple tunnels.